Análise de biografias de Einstein em dois livros de divulgação científica - Urias, Guilherme Muniz Pereira [UNESP]; Assis, Alice [UNESP] (My University, 2012)
In this paper we analyzed and compared two Albert Einstein’s biographies. The first one was “Albert Einstein and his inflatable universe”, written by Mike Goldsmith. The second biography was “Einstein – his life and universe”, written by Walter Isaacson. The intention of this comparison was to identify convergent and divergent points between two books, beyond verifying the possible neglected important points of Einstein’s life suppressed by Goldsmith to facilitate the comprehension of the text. Such details are those that we consider important to Albert Einstein’s intellectual development, and may have significantly contributed to the development of his theories. For this, our analysis was grounded in Douglas Allchin’s perspective, whose work presents aspects in the rhetoric of the text that contribute to the Science and scientist mystification.

Neste trabalho, propomos analisar e comparar duas biografias do físico Albert Einstein. A primeira foi “Albert Einstein e seu universo inflável”, escrita por Mike Goldsmith, e a segunda, “Einstein: sua vida, seu universo”, escrita por Walter Isaacson. O intuito dessa comparação é o de identificar os pontos convergentes e divergentes das duas obras, além de verificar os possíveis detalhes importantes da vida de Albert Einstein que possam ter sido negligenciados com a intenção de facilitar a compreensão dos conteú- dos abordados na obra de Goldsmith. Tais detalhes são aqueles que consideramos importantes no contexto do desenvolvimento intelectual de Albert Einstein, e que podem ter contribuído significativamente para a construção de suas teorias. Para tanto, fundamentamos a análise na perspectiva de Douglas Allchin, cujo trabalho apresenta aspectos na retórica de um texto que contribuem para a mitificação da ciência e do cientista. Palavras-chave: Divulgação científica. Mitificação da ciência.
Keywords: Popular science; Scientific myth-conceptions; Albert Einstein; Science education; Albert Einstein; Ensino de Ciências